Characterization of novel CASQ1 variants in two families with unusual phenotypic features - Laarne, Milla; Jokela, Manu; Zhao, Fang; Huovinen, Sanna; Kornblum, Cornelia; Reimann, Jens; Johari, Mridul; Vihola, Anna; Sarparanta, Jaakko; Udd, Bjarne; Hackman, Peter; Lehtokari, Vilma-Lotta; et al. (Springer Nature, 2026)
Background
Variants in CASQ1, encoding a calcium-binding protein in the fast-twitch fibers of skeletal muscle, cause sarcoplasmic reticulum aberrations such as large vacuoles with CASQ1 inclusions or, less commonly, tubular aggregates. To date, seven pathogenic variants have been described, all dominant missense variants. The typical symptoms of the disease include muscle weakness, cramps, myalgia, and fatigue.
Methods
We used genome and exome sequencing to identify the disease-causing variants in two families with dominant myopathy. The candidate variants were further characterized by cell-transfection studies and western blotting.
Results
In Family 1, three patients presented with exercise intolerance, cramps, and myalgia. Additionally, the proband had muscle weakness and her muscle biopsy showed nemaline bodies. In electron microscopy, there were morphological changes in the triads and the SR-feet in all patients. A variant in CASQ1, p.(Glu89Lys), was found in all patients, whereas the proband had also two compound heterozygous variants in NEB. In Family 2, three patients presented with progressive muscle weakness. The proband’s muscle biopsy showed marked atrophy. The frameshift variant p.(Gly383Alafs*39) in CASQ1 was found in all three patients. In silico analysis indicated that the variant results in protein extension, which was confirmed by western blotting of patient muscle. Cell-transfection studies showed that the variant protein forms aggregates.
Conclusion
This study expands the spectrum of pathogenic CASQ1 variants. The morphological changes in the SR-feet indicate a novel pathogenetic mechanism.